2000
DOI: 10.1002/1099-0682(200010)2000:10<2271::aid-ejic2271>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Ion Complexes of 2,2′-Bipyridyl-3,3′-diol and 2,2′-Bipyridyl-3-ol: Spectroscopic Properties and Solvent-Dependent Binding Modes

Abstract: The complexation behaviour of 2,2′‐bipyridyl‐3,3′‐diol and 2,2′‐bipyridyl‐3‐ol, BP(OH)2 and BPOH, with various heavy and transition metal ions has been investigated in aqueous, alcoholic, and acetonitrile solutions. Whereas the complexes with paramagnetic ions and HgII are non‐fluorescent, ZnII and CdII form highly fluorescent complexes, their coordination geometries depending on the solvent proticity and hydrogen‐bond donating ability. Through a comparative study with the corresponding chelates of 2,2′‐bipyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…To further investigate this behavior, Job plots were constructed for GPS-TBA, with I in CHCl 3 and MeCN. The contribution of I-GPS-TBA to the changes in the absorption signal of the dye-template mixture (Y λ ) was plotted against the molar ratio of GPS-TBA [57]. In CHCl 3 , it was found that 2 moles of GPS-TBA could form a complex with 3 moles of I (I:GPS-TBA 1.5:1 stoichiometry, see Figure 3a and Figure S9a, Supplementary Material).…”
Section: Interaction Of I With Gps-tba In Chcl 3 and Mecnmentioning
confidence: 99%
“…To further investigate this behavior, Job plots were constructed for GPS-TBA, with I in CHCl 3 and MeCN. The contribution of I-GPS-TBA to the changes in the absorption signal of the dye-template mixture (Y λ ) was plotted against the molar ratio of GPS-TBA [57]. In CHCl 3 , it was found that 2 moles of GPS-TBA could form a complex with 3 moles of I (I:GPS-TBA 1.5:1 stoichiometry, see Figure 3a and Figure S9a, Supplementary Material).…”
Section: Interaction Of I With Gps-tba In Chcl 3 and Mecnmentioning
confidence: 99%
“…As highly fluorescent conjugated polyarenes, alternating copolymers consisting of 1,4-diethynylbenzene and bpy units were synthesized [37]. Both linear rod-like -chain polymers, bpy-5,5'-diyl (94)(95)(96), and angularly linked polymers, bpy 4,4'-diyl (97-99, DP = 4-25), showed fluorescence in the range of 389 -456 nm ( = 0.45 -0.67 in toluene). The related model compounds (100-105) showed similar spectroscopic properties to the polymers, exhibiting quite efficient fluorescence ( ~1.0).…”
Section: Extended Oligopyridinesmentioning
confidence: 99%